Metformin treatment and risk of diabetic peripheral neuropathy in patients with type 2 diabetes mellitus in Beijing, China - Yang, Ruotong; Yu, Huan; Wu, Junhui; Chen, Hongbo; Wang, Mengying; Wang, Siyue; Qin, Xueying; Wu, Tao; Wu, Yiqun; Hu, Yonghua (Frontiers in Endocrinology, 2023)
Background: Metformin treatment is associated with vitamin B12 deficiency, which is a risk factor for neuropathy. However, few studies explored the relationship between metformin treatment and diabetic peripheral neuropathy (DPN), and existing findings are contradictory. We aimed to assess whether metformin therapy is associated with DPN in patients with type 2 diabetes mellitus (T2DM) in Beijing, China. Methods: All newly diagnosed T2DM patients were included in the Beijing Medical Claim Data for Employees database from January 2010 to September 2012. Metformin treatment was defined as metformin prescription records for patients. The daily dose was calculated both as continuous and categorical variables. DPN was defined as hospitalized DPN cases in the database that occurred after the diagnosis of T2DM. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Among 49,705 T2DM patients, 1,933 incident cases of DPN were recorded during a median follow-up of 6.36 years. Crude incidence rates were 7.12 and 3.91 per 1000 person-years for patients who received metformin treatment (N=37,052) versus those who did not (N=12,653), respectively. Patients with metformin therapy had a higher risk of DPN than those who did not use metformin, with an adjusted HR of 1.84 (95% CI, 1.62, 2.10). The average daily dose was positively associated with DPN risk (HR, 1.48; 95% CI, 1.46, 1.51; P for trend <0.001). Patients with daily doses of 1.0-2.0 g and >2.0g had a 1.53-fold (1.30, 1.81) and 4.31-fold (3.76, 4.94) higher risk of DPN than patients not receiving metformin, respectively. Patients who were younger than 60 years old were at higher risk for DPN (P <0.05 for interaction test). Among patients taking vitamin B12 at baseline, there was no increased risk of DPN in the metformin group (1.92: 0.79, 4.69). Conclusions: Metformin treatment was associated with an increased risk of hospitalization for DPN in Chinese patients with T2DM, and the risk was positively dose-responsive to the daily dose of metformin. In particular, metformin use was a major risk factor for DPN in younger patients. Concomitant vitamin B12 use may avoid the increased DPN risk associated with metformin use.